Volyn Region in the Period of Combat Actions Deployment on the Eastern Front of the World War I (1914–1916) - Demianiuk, Oleksandr; Soliar, Ihor (Український історичний журнал, 2022)
Volyn region, western districts of which became a place for a constant combat struggle starting from 1915, severely suffered during the World War I. The region was crowded by the militaries from both sides, and this reflected on the condition of the locals. On the other hand, several military operations conducted in Volyn region have been eternalized in the military craft handbooks. Purpose of the research is to conduct assessment of the World War I events as to their impact on the separate region, in particular – Volyn region, and to trace the course of episodes of the Great War during, first of all, 1915–1916, a period when Volyn finally entered the theatre of the combat actions. Research methodology is based upon the general methods of analysis, synthesis, and generalization. It is also based upon the principles of critical analysis of archive and documentary sources and methods of comparative analysis of the sources and historiography. Scientific novelty is in the fact that the authors confirmed the general tendencies of how the World War I deployed in Volyn region and formulated the peculiarities of the separate aspects of the military events occurring there during 1914–1916 (based on the little-known or even unknown documents from the archives of the Volyn, Zhytomyr and Rivne region). Conclusions. Volyn region, which from the beginning of the World War I received a frontline status, for several years became a place of, firstly, active (1915–1916) and, then, permanent (1917–1918) combat actions. A considerable amount of the local male population was conscripted to the Russian army, whereas most of the state authorities of the western districts and local population were evacuated deeply into the Russian Empire. The regional infrastructure was severely damaged, while most of the settlements in the area of the combat actions were destroyed with local citizens being relocated to both sides of the front.